2020
DOI: 10.1074/mcp.ra120.002028
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-linking Mass Spectrometry Approach Defines Protein Interactions in Yeast Mitochondria

Abstract: Protein cross-linking and the analysis of cross-linked peptides by mass spectrometry is currently receiving much attention. Not only is this approach applied to isolated complexes to provide information about spatial arrangements of proteins, but it is also increasingly applied to entire cells and their organelles. As in quantitative proteomics, the application of isotopic labeling further makes it possible to monitor quantitative changes in the protein-protein interactions between different states of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 124 publications
(207 reference statements)
2
66
1
Order By: Relevance
“…The water soluble, amine‐amine bifunctional crosslinker, bis(sulfosuccinimidyl)suberate (BS3), has previously been successfully used for the XL‐MS analysis of mitochondrial proteins [53]. BS3 has an arm length of 11.4 Å, providing a medium length range for crosslinking of TIM22 components.…”
Section: Resultsmentioning
confidence: 99%
“…The water soluble, amine‐amine bifunctional crosslinker, bis(sulfosuccinimidyl)suberate (BS3), has previously been successfully used for the XL‐MS analysis of mitochondrial proteins [53]. BS3 has an arm length of 11.4 Å, providing a medium length range for crosslinking of TIM22 components.…”
Section: Resultsmentioning
confidence: 99%
“…A much chosen subject of study concerns PPIs in isolated mitochondria represented in Table 1 by five recent examples [13][14][15][16][17]. There is partial overlap between the PPIs identified in these studies, but the fraction of identified inter-protein cross-linked peptides varied from about 3% to about 60%.…”
Section: Recent Publications Using Cxms For Ppi Discovery In Complex Systems Reveal Discrepancies In Error Assessmentmentioning
confidence: 99%
“…Furthermore, FDR can be expressed at different levels, varying from the cross-linked spectrum (CSM) level down to the PPI level (section 4) [10,15,20]. The different levels used to express the FDR in similar types of CXMS studies like the mitochondrial interactome examples [13][14][15][16][17] has been confusing. It underscores the importance of the summons of the CXMS community for the development of standards for reliable FDR estimation for inter-protein peptide pairs [6].…”
Section: Recent Publications Using Cxms For Ppi Discovery In Complex Systems Reveal Discrepancies In Error Assessmentmentioning
confidence: 99%
See 2 more Smart Citations